PENDIDIKAN KESEHATAN TENTANG PENULARAN TUBERKULOSIS TERHADAP STIGMA MASYARAKAT WISATAWAN TENTANG TUBERKULOSIS - Gede Ngurah (Jurnal Gema Keperawatan, 2018)
This research aimed at knowing the effect of education about tuberculosis on the social tourism stigma about tuberculosis at Kuta Village tourism in Badung. This research used pra experiment method with the one grup pretest postest design by using non probability sampling with total sampling. The number of sample is 30 respondent. The data obtained were analyzed with One Sample T test, from the statistical analysis obtained sig 0,000 (palpha (0,05)) on the social tourism stigma about tuberculosis contamited which means there is less influence of health education on the social tourism stigma about tuberculosis contamined at Kuta Village tourism in Badung.